2009
DOI: 10.1186/1472-6963-9-110
|View full text |Cite
|
Sign up to set email alerts
|

Participant observation of time allocation, direct patient contact and simultaneous activities in hospital physicians

Abstract: Background: Hospital physicians' time is a critical resource in medical care. Two aspects are of interest. First, the time spent in direct patient contact -a key principle of effective medical care. Second, simultaneous task performance ('multitasking') which may contribute to medical error, impaired safety behaviour, and stress. There is a call for instruments to assess these aspects. A preliminary study to gain insight into activity patterns, time allocation and simultaneous activities of hospital physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 41 publications
3
81
1
6
Order By: Relevance
“…We examined tasks and documentation use during the encounter and interviewed participants about their preferences. Our finding that a large percent of time in an ED clinical encounter is spent on documentation activities (65%) is similar to those of other studies in which documentation activities ranged from 23% to 59% of the encounter [7,12,14]. Our results also suggest a considerable amount of documentation is performed while the physician is performing another activity in parallel.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We examined tasks and documentation use during the encounter and interviewed participants about their preferences. Our finding that a large percent of time in an ED clinical encounter is spent on documentation activities (65%) is similar to those of other studies in which documentation activities ranged from 23% to 59% of the encounter [7,12,14]. Our results also suggest a considerable amount of documentation is performed while the physician is performing another activity in parallel.…”
Section: Discussionsupporting
confidence: 90%
“…Efficiency and physician time are critical, particularly in EDs [9,10]. Emergency physicians often multi-task and frequently transition between activities quickly and unexpectedly while simultaneously handling multiple patients and frequent interruptions [11,12]. In addition, ED patient acuities and patient volumes vary, influencing the ways in which physicians perform routine tasks [13].…”
mentioning
confidence: 99%
“…[1][2][3]5,6 Similarly, we found that physicians spent 5.3 minutes per patient-about 13% of an 8-hour shift. We also found that communication times varied substantially by provider, from a mean of 2 minutes per patient to greater than 12 minutes per patient.…”
Section: Discussionsupporting
confidence: 55%
“…Studies conducted at single institutions in the US [1][2][3] and elsewhere [4][5][6] have found that hospitalists generally spend little time communicating with their patients, and that there is often disagreement between doctors and both nurses and patients about the plan of care. 7,8 However, it is not known how much time physicians actually spend communicating with nurses and other physicians, and more importantly, whether more time spent communicating is associated with higher levels of agreement regarding the plan of care or greater patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 142 papers were excluded based on the title and abstract, leaving 93 full-text papers to be screened for eligibility. Of these, 75 papers were excluded as they did not fit the inclusion criteria and two papers were unobtainable, even though interlibrary requests were submitted and the authors were contacted, leaving 16 papers [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] included in the review ( Table 9). …”
Section: Health Economic Study Methods and Resultsmentioning
confidence: 99%